Improving Qur'anic Reading Skills at Reysha Mulya Cendekia Qur'an Learning Center Pekanbaru - Ahmad Hafizon; Maralottung Siregar; Siti Halimah; Neni Neni (International Journal of Community Service Implementation, 2025)
This community service activity aims to improve Qur'anic reading skills, particularly in the areas of tajweed and the articulation of makhraj (letter pronunciation), among children at Reysha Mulya Cendekia Qur'an Learning Center in Pekanbaru. The program includes several main activities, such as Qur'an recitation improvement (tahsin), tajweed training, as well as monitoring and evaluation of student progress. Initial observations revealed that many students still struggle with proper pronunciation of Arabic letters and understanding the rules of tajweed. Therefore, this service program was designed to provide intensive training through regularly scheduled guidance sessions, held three times a week. The results of the program are: 1) method of implementation. the stages of implementation consisted of the following steps: a) initial observation, b) needs assessment, c) tajweed training program, d) ongoing evaluation.2) challenges in teaching tajweed and qur’anic reading, a) lack of basic mastery among children,b) low motivation and learning spirit, c) lack of variety in teaching methods, d) limited learning facilities and media, e) shortage of teaching staff, f) lack of parental support at home. Through ongoing evaluation, this activity is expected to bring even greater positive impacts for future generations, particularly in their understanding and practice of the teachings of the Qur’an